2005
DOI: 10.1063/1.1887823
|View full text |Cite
|
Sign up to set email alerts
|

SiO 2 ∕ PbTe quantum-dot multilayer production and characterization

Abstract: We report the fabrication of multilayer structures containing layers of PbTe quantum dots (QDs) spaced by 15–20 nm thick SiO2 layers. The QDs were grown by the laser ablation of a PbTe target using the second harmonic of Nd:YAG laser in an argon atmosphere. The SiO2 layers were fabricated by plasma chemical vapor deposition using tetramethoxysilane as a precursor. The influence of the ablation time on the size and size distribution of the QDs is studied by high-resolution transmission electron microscopy. Opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…5 IV-VI QDs have been fabricated by molecular beam epitaxy and other synthesis methods. 2,[6][7][8] Recently, Heiss et al 9 demonstrated that PbTe QDs could be fabricated by annealing PbTe͑001͒ / CdTe͑001͒ single quantum well structures at different temperatures and observed room-temperature midinfrared photoluminescence with intensities significantly higher than those observed from their best PbTe bulk or quantum well samples. Transmission electron microscopy characterization showed that the PbTe/ CdTe QDs had a highly symmetric geometry of a small-rhombo-cubooctahedron with three interface classes ͕100͖, ͕110͖, and ͕111͖ around the periphery of the dots ͓see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…5 IV-VI QDs have been fabricated by molecular beam epitaxy and other synthesis methods. 2,[6][7][8] Recently, Heiss et al 9 demonstrated that PbTe QDs could be fabricated by annealing PbTe͑001͒ / CdTe͑001͒ single quantum well structures at different temperatures and observed room-temperature midinfrared photoluminescence with intensities significantly higher than those observed from their best PbTe bulk or quantum well samples. Transmission electron microscopy characterization showed that the PbTe/ CdTe QDs had a highly symmetric geometry of a small-rhombo-cubooctahedron with three interface classes ͕100͖, ͕110͖, and ͕111͖ around the periphery of the dots ͓see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We reported here characterization and electrochemical properties of an ultrathin layer of Pt (ULPt) prepared by the PLD method, and its application to detect hydrogen peroxide. The PLD method is widely used to deposit a functional thin film like a superconductive solid film [13], an electrolyte film for solid oxide fuel cell (SOFC) [14], and multilayers in an atomic layer with high quality [13,15,16]. Quality of the film is comparable to those grown by molecular beam epitaxy (MBE).…”
Section: International Journal Of Electrochemistrymentioning
confidence: 99%
“…To conquer these problems, physical way of multilayer approach using layer by layer deposition process is preferred. Meantime, PbTe NCs prepared by multilayer approach using physical method such as molecular beam epitaxy [16] and thermal evaporation [17] are less studied compared to other Lead chalcogenides. Thermal evaporation is a simple, cost effective and versatile method to form complex nanocomposite structures with fine control over thickness through alternate layer by layer deposition.…”
Section: Introductionmentioning
confidence: 99%